2016
DOI: 10.1111/deci.12233
|View full text |Cite
|
Sign up to set email alerts
|

Trial or No Trial: Supplying Costly Signals to Improve Profits*

Abstract: Many software and video game firms offer free trials with limited content to help buyers assess the likely value of the goods that they may purchase. This article examines fundamental issues related to the incentives and risks for a monopoly by providing a trial. Assuming that a seller can control the mix of components in a trial, we introduce a new mechanism for buyers’ inference of using a trial. We find that a trial may enable the seller to segment the market and charge a higher price to high‐valuation buye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Businesses find benefits in free trials and services in different ways. For example, Li and Yi (2017) studied software and video game firms' free trials and found that a trial may enable the seller to segment the market and charge a higher price to high-valuation buyers, although free trials can also cause a decline in demand. Ajorlou et al (2018) found that, while both buyers and non-buyers contribute to information diffusion, buyers are more likely to spread the news about the product and suggested that companies use free offers, as seen in the smartphone app market, to attract low-valuation customers and to get them more engaged in the information spread so that they can reach potential high-valuation consumers in parts of the social network that would otherwise remain untouched without the price drops.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Businesses find benefits in free trials and services in different ways. For example, Li and Yi (2017) studied software and video game firms' free trials and found that a trial may enable the seller to segment the market and charge a higher price to high-valuation buyers, although free trials can also cause a decline in demand. Ajorlou et al (2018) found that, while both buyers and non-buyers contribute to information diffusion, buyers are more likely to spread the news about the product and suggested that companies use free offers, as seen in the smartphone app market, to attract low-valuation customers and to get them more engaged in the information spread so that they can reach potential high-valuation consumers in parts of the social network that would otherwise remain untouched without the price drops.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing research also suggests that quality and completeness of free offers affect customer retention. For example, Li and Yi (2017) found that, if the free trial deviates from the true nature of the full product, buyers may feel "cheated" by the trial provider, which might lead to a negative image of the brand and less likelihood of customer retention beyond the free period. Additionally, Li et al (2019) examined how quality and other design factors of the free sample affect profit generated by the product or service in the context of a book publisher that provides free samples for the books it sells online and found that free samples of the entire content, instead of partial samples, can be very effective in increasing revenues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Zhang et al (2016) suggested that it was necessary to control the functionalists of free trial product to avoid cannibalization effect. Li and Yi (2017) indicated that the size and content of the trial version and the distribution of user's prior belief would affect the free trial ability of IT products and services to convey information so that it made a difference in user's valuation on trial. The recent popular practice is that IT companies offer the users with basic functions freely and charge them for advanced or additional functions (Hamari et al, 2017;M€ antym€ aki and Islam, 2015;Liu et al, 2014).…”
Section: 22mentioning
confidence: 99%
“…It usually refers to IT companies offering users free access to experience their products and services, either with restricted function or with full-fledged version in a limited period. Users are allowed to opt out or stay after trial without penalty in order to stimulate and convince user's intention of adoption and purchase (Cheng and Tang, 2010; Foubert and Gijsbrechts, 2016; Li and Yi, 2017; Yang et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation